Military order as a legal form of operation of organizational units military administration in the sphere of internal organization - Wasilewski Krystian (2024)
examine the legal basis on which managerial acts, such as orders, may be issued and the extent to which they may regulate the conduct of employees. In practice, the Act on Homeland Defense raises doubts regarding the scope of introducing orders towards employees who are not soldiers. The fundamental problem is to determine whether the issuance of such acts falls within the scope of the powers of the managing entity, and how such acts may affect the rights and obligations of employees.